Heterogeneity in resistance training induced muscle strength and mass responses in the upper and lower extremities - Ylijärvi, Sara (2023)
It has been reported that some muscle groups may demonstrate higher strength and hypertrophic gains in response to resistance training than others. In addition to this, the gains in strength and muscle size are highly individual. The purpose of this master’s thesis is to investigate how the strength and hypertrophic adaptations compare between the elbow flexors and knee extensors in response to similar resistance training regimens. A further purpose is to study the interindividual variability in the strength and hypertrophic responses and to investigate the connection of the responses between the muscle groups.